Perspektif Gender dan Green Behavior dalam Keputusan Pembelian Produk Kuliner di Kota Denpasar - Ayu Muliani, Ni Komang; Wijaya, Putu Yudy; Trarintya, Mirah Ayu Putri (Widya Manajemen, 2025)
The culinary industry is growing rapidly due to lifestyle and supply of community behavior. Urban communities tend to behave by buying food rather than cooking. This study aims to analyze the effect of green knowledge and green marketing on purchasing interest and purchasing decisions for culinary products in Denpasar City, and to analyze the differences in their influence based on gender perspective. The population is the population of Denpasar City, with a sample size of 385 people, purposive sampling technique, using SEM-PLS with MGA (multi-group analysis) as an analysis technique. The results showed that Green knowledge had a significant effect, while green marketing did not have a significant effect on purchasing decisions. Green knowledge and green marketing had a significant effect on purchasing interest, and purchasing interest had a significant effect on purchasing decisions. Purchasing interest was able to mediate green knowledge and green marketing on purchasing decisions. Male customers had a stronger influence between green knowledge on purchasing decisions and purchasing interest. Female customers have a stronger influence between green marketing on purchase intention, while the influence of green marketing on purchasing decisions of male customers has a stronger influence than female customers.